Effects of Teachers’ Participation in Decision-Making on Organisational Commitment in Ghanaian Basic Schools - Abonyi, Usman Kojo (Papers in Education and Development, 2024)
This study investigated the effects of teachers’ participation in decision-making in Ghanaian basic schools on their organisational commitment. The study utilised a descriptive survey design to randomly select 285 teachers from the La Nkwantanang-Madina Municipality of the Greater Accra region of Ghana to participate in the research. The generated data were analysed using descriptive statistics (means and standard deviations), confirmatory factor analysis, and structural equation modelling. The results showed that teachers moderately participated in school decision-making. Similarly, their level of organisational commitment to the teaching profession was moderate. Finally, the effect of teacher participation in decision-making on organisational commitment was positive and statistically significant. The study’s findings suggest that implementing shared leadership models, where teachers are consistently involved in discussions about school policies, curriculum development, and other critical areas, can enhance their commitment and performance. Consequently, the study recommends that school leaders initiate pragmatic policies to promote teachers’ participation in decision-making, thereby increasing their organisational commitment. Keywords: Participative decision-making, teacher engagement, school decision-making, organisational commitment, teacher participation